2017
DOI: 10.15832/ankutbd.447704
|View full text |Cite
|
Sign up to set email alerts
|

Pre-harvest Application of ReTain (Aminoethoxyvinylglycine, AVG) Influences Pre-harvest Drop and Fruit Quality of ‘Williams’ Pears

Abstract: Williams' is the highly quality pear cultivar mostly produced in the Eğirdir region of Turkey. ReTain (15% aminoethoxyvinilglycine, AVG) is a plant growth regulator used to control pre-harvest drop and increase fruit weight and firmness. The objective of this study was to determine the responses of AVG treatments on the preharvest drop and fruit quality of 'Williams' pear. Pear trees of the cultivar 'Williams' were sprayed 30, 21 and 7 days before commercial harvest (DBH) with AVG, at doses of 100, 125 and 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Increased levels of WL during storage could also be a result of increased rates of respiration [ 65 ]. Previous reports have also indicated that AVG improved fruit firmness in sweet cherry [ 13 ], pear [ 21 ], and apple [ 12 , 22 ]. In addition, SA-treated fruit recorded a small reduction in WL ( Figure 2 ), which was associated with improved fruit firmness ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Increased levels of WL during storage could also be a result of increased rates of respiration [ 65 ]. Previous reports have also indicated that AVG improved fruit firmness in sweet cherry [ 13 ], pear [ 21 ], and apple [ 12 , 22 ]. In addition, SA-treated fruit recorded a small reduction in WL ( Figure 2 ), which was associated with improved fruit firmness ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, the applications of SA and chitosan were generally the second and third most effective treatments, compared to the control. It has been reported that the application of AVG significantly delayed starch degradation and reduced SSC, but enhanced acidity in sweet cherry [ 13 ], pear [ 21 , 34 ], and apple [ 12 , 22 ]. Similarly, SA was proven to delay the ripening and senescence process of plum [ 46 ], apricot [ 20 , 49 ], and mango fruit [ 40 ], represented by low SSC and high organic acid contents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It also influences the reduction of fruit drop [7], the improvement of the total yield [8], and the maintenance of fruit quality in apricots [9], apples [10], sweet cherries [11], and pears [12]; the response of different cultivars can vary significantly [13] and also depends on the dose applied [14].…”
Section: Introductionmentioning
confidence: 99%